2004
DOI: 10.1023/b:mcbi.0000028747.92084.42
|View full text |Cite
|
Sign up to set email alerts
|

Effects of  -lipoic acid supplementation on maternal diabetes-induced growth retardation and congenital anomalies in rat fetuses

Abstract: The mechanism of diabetic embryopathy is not known. Excessive reactive oxygen species (ROS) produced in diabetes may be causally related to foetal anomalies. The objective of this study was to determine whether supplementation with the antioxidant lipoic acid (LA) could prevent maternal diabetes-related foetal malformations and intrauterine growth retardation (IUGR) in rats. Pregnant rats were non-treated (Group I) or made diabetic on gestation day (GD) 2 by injecting streptozotocin (Group II). Group III was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 54 publications
4
33
0
Order By: Relevance
“…Maternal diabetes entails embryo maldevelopment, leading to increased perinatal pathological situations, such as microsomias and congenital malformations (3,26), that are obvious from earlier stages of pregnancy according to our results and other previous works (10,49). Along these lines, we observed both an increased percentage of malformed embryos (4-fold increase on gestational day 13) and retarded growth in normal embryos from diabetic mothers.…”
Section: Discussionsupporting
confidence: 89%
“…Maternal diabetes entails embryo maldevelopment, leading to increased perinatal pathological situations, such as microsomias and congenital malformations (3,26), that are obvious from earlier stages of pregnancy according to our results and other previous works (10,49). Along these lines, we observed both an increased percentage of malformed embryos (4-fold increase on gestational day 13) and retarded growth in normal embryos from diabetic mothers.…”
Section: Discussionsupporting
confidence: 89%
“…After the animals were killed, it was observed that the uteruses of diabetic female rats that did not deliver offspring revealed the presence of resorptions sites, indicating that chronic hyperglycemia in the intrauterine environment caused by maternal diabetes negatively affected offspring development and survival since the moment of conception. A recent study also reported an elevation in the rates of embryo resorption and fetal death among the offspring of diabetic female rats (26).…”
Section: Discussionmentioning
confidence: 87%
“…Supplementing the maternal diet with LA failed to rescue Lias Ϫ/Ϫ mice from embryonic lethality, although it is likely that LA can cross the placenta efficiently, since Al Ghafli et al have demonstrated that LA supplementation (20 mg kg Ϫ1 , given intraperitoneally) improved the survival of embryos in rats with diabetes induced by streptozotocin during the pregnancy (1).…”
Section: Discussionmentioning
confidence: 99%